Sam Fox library orchestra folio No.1, cello - MILES, Walter E. [et.al] (Sam Fox Pub., 1912)
SparkletsnBasket of rosesnEleanornValse DanseusenA garden dancenBowl of [ansiesn At sunsetnDancing leavesnWater liliesnMon plaisirnIn poppylandnDream of the flowers